Extreme Weather and Poverty Risk : Evidence from Multiple Shocks in Mozambique - Baez, Javier E. (World Bank, Washington, DC, 2018)
This paper investigates the effects of multiple weather shocks on household welfare in Mozambique, as well as some of the coping responses and price mechanisms at play. The analysis employs a triple-difference strategy that exploits variation in the shocks across space, time, and cropping cycles. The findings demonstrate high levels of vulnerability across various weather risks. Experiencing a cyclone, flood, or drought leads to a drop of up to 25-30 percent in per capita food consumption and around 0.4 fewer meals per day per person. Poverty increased by 12 and 17.5 percentage points in two of the three events analyzed. Human capital accumulation, as measured by school participation and morbidity, is disrupted. Households follow risk-coping strategies, such as increasing the labor supply of their children or selling assets, which entail partial protection in the aftermath of the shock at the cost of lower income growth in the future. In disentangling the channels, the paper shows that maize prices exhibit higher volatility in food markets that are spatially close to the most affected areas. The results are robust to several robustness checks, including analysis of bias from selective migration, and indicate that household welfare and economic mobility in low-income environments are constrained by uninsured weather risks.